The solubility and water sorption properties of a combination of Ca(OH)2and propolis when used as pulp capping material - Nirawati Pribadi; Veronica Regina Rosselle; Nanik Zubaidah; Ira Widjiastuti (Wolters Kluwer Medknow Publications, 2020)
Background: Calcium hydroxide [Ca(OH)2] is a material used during pulp capping treatment, despite being readily soluble in both water and acid. In contrast, propolis constitutes a nontoxic resin which is not easily dissolved in water. Therefore, a combination of Ca(OH)2and propolis is assumed to be capable of increasing the mechanical properties of Ca(OH)2and to diffuse into the dentinal tubules. Objective: This research aimed to reveal the solubility and water sorption ability of a combination of Ca(OH)2and propolis as pulp capping material. Materials and Method: The samples comprised 18 Ca(OH)2and Ca(OH)2-propolis chips, 15 mm × 1 mm in dimension, all of which were stored in an incubator for 24 h at 37°C. Each sample was then divided into two groups: one dissolved in 50 mL of artificial saliva for 24 h at 37°C and another for 7 days before being weighed, dried, incubated, and weighed for a second time. The result of the reduction in mass divided by the volume of the samples was considered to constitute the level of solubility and water sorption. The difference between the solubility and water sorption ability was analyzed using an independent t-test with significant difference <0.05. Results: The solubility of Ca(OH)2-propolis is lower than that of Ca(OH)2 after immersion for 1 day (P = 0.001) and 7 days (P = 0.000). The water sorption ability of Ca(OH)2-propolis is no different than that of Ca(OH)2after immersion for 1 day (P = 0.088) and 7 days (P = 0.635). However, the water sorption ability of Ca(OH)2-propolis after 1-day immersion is higher than immersion for 7 days (P = 0.012). Conclusion: The solubility Ca(OH)2-propolis is lower than that of Ca(OH)2, but its water sorption is higher than that of Ca(OH)2.